The Papua Conflict: The Different Perspectives of The Indonesian Government and International Communities—Review from The English School Theory - Rosyidin, Mohamad; Dir, Andi Akhmad Basith; Wahyudi, Fendy Eko (UI Scholars Hub, 2022)
The West Papuan issue has become a flashpoint of conflict between Indonesia and the international community. However, studies on this subject have never been concerned about the causal root of differences between Indonesia and the international community over the West Papuan issue. There has not been a theoretical account of how this issue is framed in international politics. Existing literature tends to overlook the fundamental narrative, that is, the contrasting view between Indonesia and those who support West Papuan freedom. This paper aims to analyse the root cause of this debate. Using the English School approach in international relations, this paper argues that Indonesia frames this issue within the concept of ‘sovereignty’ and norms of ‘non-interference’, which represent the Pluralist strand. On the contrary, the international community represented by Pacific countries and civil societies frames this issue within the concept of ‘human rights’ and norms of ‘self-determination’, representing the Solidarist strand.